Esterification of free fatty acids in simulated waste oil using novel solid acidic ionic liquid as catalyst - Shabirah, Ezan (2014)
Issues on petroleum-based fuel shortage can be overcome by producing biodiesel fuel-type or also known as fatty acid methyl ester (FAME). The uses of biodiesel can improve the environmental health and also decrease the worries on the sustainability concerns on world sources of energy (i. e. natural gases). In this study waste cooking oil (WCO); a non-edible type of feedstock was used due to its availability and low cost. Nevertheless, WCO basically has high free fatty acids (FFAs) content which is in the range of 6-15%. Therefore, the study on the esterification of FFAs in a feedstock (WCO) using novel solid acidic ionic liquid as catalyst is carried out to lower the free fatty acid in the WCO. In this case, the use of heterogenous type of acid catalyst is more preferable in the esterification process due to its efficiency. The Bronsted acid ionic liquids (ILs) triethylammonium hydrogen sulphate (Et3NHSO4) is chosen to immobilize with solid support, divinylbenzene (DVB) polymer so that it will make separation process smoother and can increase its reusability as a catalyst. The novel solid acidic ionic liquid polymer has been synthesized based on Nuclear Magnetic Resonance (1H-NMR), Elemental Analysis CHNSO and Scanning Electron Microscopy (SEM). The NMR spectroscopic data for the IL sample was: 1H-NMR (500 MHz, DMSO) (ppm): δ 1.08-1.11 (triplet, 0.28H), 1.20-1.23 (triplet, 9.04H), 2.06 (singlet, 0.11H), 2.10 (singlet, 0.03H), 3.09-3.14 (sextet, 6.15H), 3.38-3.4 (doublet, 0.1H), 8.95 (singlet, 1H), 11.00 (singlet, 3.19H). The esterification of the FFA of the WCO was carried out using Et3NHSO4 as the catalyst in the first stage at the optimum reaction condition of 60°C reaction temperature, 5 wt % catalysts loading and 6:1 methanol to WCO molar ratio for three hours of reaction time. The novel solid acidic ionic liquid, Et3NHSO4 supported with DVB display good performance by showing 75.94 % FFA conversion. It was expected that the recycled catalyst will display the same properties with the fresh catalyst due to its properties that can ease the separation process from the reaction mixture. However, the FTIR result shows the difference of IR spectrum data obtained for the fresh catalyst and spent catalyst which indicates that the catalyst was fully separate from the mixture.